Collaborative Governance in the Management of the Bogor Halimun Salak Geopark - Assayuti, Muhammad Jalaludin; Rahmawati, Rita; Salbiah, Euis; Pratidina, Ginung; Lydon, Novel Anak; Wahyudin, Cecep (Administratie: Jurnal Administrasi Publik, 2025)
The Bogor Halimun Salak Geopark is a conservation area that integrates geological richness, biodiversity, and local cultural heritage. Located in Bogor Regency, it serves as a hub for environmental education and preserving Kasepuhan traditions. Despite its potential, the geopark's management encounters complex challenges, particularly in actor collaboration. This study explores the implementation of collaborative governance in geopark management and identifies factors influencing its effectiveness. A descriptive quantitative method was used with a saturated sampling of 58 respondents, consisting of government officials and local community members. Data collection involved interviews, observations, literature review, documentation, and Likert-scale questionnaires. Findings indicate that collaborative governance falls within the "good" category, with an average score of 3.81 from government employees and 3.48 from the community. The leadership dimension received the highest score, highlighting the critical role of leaders in fostering cooperation. However, initial collaborative conditions, particularly at the community level, remain weak. Identified barriers include poor cross-sector coordination, conflicting interests between tourism and mining, limited budgets, and low community participation. To address these issues, the study recommends enhancing stakeholder synergy, forming a dedicated management unit, and establishing structured collaborative frameworks. Strengthening these aspects is essential to achieve inclusive and sustainable geopark management.